Discovery of Novel Genetic Risk Loci for Acute Central Serous Chorioretinopathy and Genetic Pleiotropic Effect With Age-Related Macular Degeneration - Feng, Lei; Chen, Si; Dai, Huatuo; Dorajoo, Rajkumar; Liu, Jianjun; Kong, Jinfeng; Yin, Xianyong; Ren, Yunqing (Frontiers in Cell and Developmental Biology, 2021)
Background: Central serous chorioretinopathy (CSC) is a severe and heterogeneous chorioretinal disorder. Shared clinical manifestations between CSC and age-related macular degeneration (AMD) and the confirmation of CFH as genetic risk locus for both CSC and AMD suggest some common pathophysiologic mechanisms between two diseases. Methods: To advance the understanding of genetic susceptibility of CSC and further investigate genetic pleiotropy between CSC and AMD, we performed genetic association analysis of 38 AMD-associated single nucleotide polymorphisms (SNPs) in a Chinese CSC cohort, consisting 464 patients and 548 matched healthy controls. Results: Twelve SNPs were found to be associated with CSC at nominal significance (p < 0.05), and four SNPs on chromosomes 1, 4, and 15 showed strong associations whose evidences surpassed Bonferroni-corrected significance (rs1410996, odds ratios (OR) = 1.47, p = 2.37 × 10-5; rs1329428, OR = 1.40, p = 3.32 × 10-4; rs4698775, OR = 1.45, p = 2.20 × 10-4; rs2043085, OR = 1.44, p = 1.91 × 10-4). While the genetic risk effects of rs1410996 and rs1329428 (within the well-established locus CFH) are correlated (due to high LD), rs4698775 on Chr4 and rs2043085 on Chr15 are novel risk loci for CSC. Polygenetic risk score (PRS) constructed by using three independent SNPs (rs1410996, rs4698775 and rs2043085) showed highly significant association with CSC (p = 2.10× 10-7), with the top 10% of subjects with high PRS showing 6.39 times higher risk than the bottom 10% of subjects with lowest PRS. Three SNPs were also found to be associated with clinic manifestations of CSC patients. In addition, by comparing the genetic effects (ORs) of these 38 SNPs between CSC and AMD, our study revealed significant, but complex genetic pleiotropic effect between the two diseases. Conclusion: By discovering two novel genetic risk loci and revealing significant genetic pleiotropic effect between CSC and AMD, the current study has provided novel insights into the role of genetic composition in the pathogenesis of CSC.